Adventura Alaska Brasil - Carroll, William (Raton, NM Coda Publications, 2003)
An American couple's adventurous 125 days and 24,876 miles of exploration while driving a Mercury coupe from Anchorage, Alaska, to Brazil's Rio de Janeiro.
Preface - Detroit to Alaska - Into Alaska - Return to the 48 - Mexico - Guatemala - El Salvador - Honduras - Nicaragua - Costa Rica - Panama - The Santa Flavia - Venezuela - Columbia - Ecuador - Peru - Chili - Argentinia - Uruguay - Brasil
Keywords: Travel -- North America -- -automobile; Travel -- Central America -- automobile; Travel -- South America -- automobile